ALTERASI DAN MINERALISASI PADA DAERAH SUB-PROJECT S, BLOK A, PT SUMBAWA BARAT MINERAL, KABUPATEN SUMBAWA BARAT, PROVINSI NUSA TENGGARA BARAT: ALTERATION AND MINERALIZATION IN SUB-PROJECT S AREA, BLOCK A, PT SUMBAWA BARAT MINERAL, WEST SUMBAWA DISTRICT, WEST NUSA TENGGARA PROVINCE - Nugroho, Ariel Dwiyanto; Shiddiq, Asep Mohamad I; S. J. Suprapto; Handayani, Tatik; Sahidin (Buletin Sumber Daya Geologi, 2024)
The research area is located in the Mining Business License (IUP) owned by PT Sumbawa Barat Mineral located in Taliwang, West Sumbawa, West Nusa Tenggara, located on the Sunda-Banda Arc magmatic line which shows the potential for metal mineralization resulting from hydrothermal activity in the research area, the potential for mineralization spread in the research area is epithermal type. This research aims to determine the alteration, mineralization and type of depositethat develops in the research area. The methods used in this research are geological mapping with grid mapping method and grab sampling, XRF analysis by looking for elemental content, petrography analysis to determine the texture and structure of rocks and minerals, mineragraphy analysis to determine the kind of metallic minerals, and XRD analysis to identify alteration minerals in more detail. The results of this research show the presence of propylitic, argillic, advanced argillic, and silicified alteration. With mineralization of silver, copper, lead, zinc, arsenic, and manganese with the presence of covellite minerals, and dickite, the mineralization type of the research area is intermediate depth high sulfidation epithermal type.